Workshops in Vienna University Library - Popović, Aleksandra (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
The stay in Vienna within the Tempus project UMI JEP 16059-2001 began with a visit to the University and the University Library in Vienna. During the five working days of our stay, we have systematic discussions on interesting subjects from librarianship and we made several working visits to faculty and other university libraries in Vienna.